PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, ASSETS GROWTH, CURRENT RATIO, DAN TOTAL ASSETS TURNOVER TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tanty Khairunnisa; Taufik Taufik; K. M. Husni Thamrin (JEMBATAN, 2019)
This research aimed to recognize the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), Assets Growth, Current Ratio (CR), and Total Assets TurnOver (TATO) To Price To Book Value (PBV) at Food and Beverage sector was registered on Indonesia Stock Exchange. This research using secondary data from company financial statement. The Population on this research are 33 companies. Sampling method used purposive sampling by taking 14 companies. This study used multiple linier regression analysis. The result showed that DER, ROA, Assets Growth, and TATO had a positive effect an PBV, while CR has no effect.Keywords: Current Ratio (CR), Debt to Equity Ratio (DER), Growth, Price to Book Value (PBV) , Return On Assets (ROA), dan Total Assets TurnOver (TATO)